Can Electronic Evidence Constitute Sufficient Grounds for Criminal Liability? - Suryana, Atang; Sakmaf, Marius Suprianto (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The advancement of information technology has triggered a paradigm shift in the evidentiary system of criminal law, particularly concerning the legality and authenticity of electronic evidence. This study seeks to examine the legal standing of electronic evidence within the Indonesian criminal procedure framework, assess the impact of Constitutional Court Decision No. 20/PUU-XIV/2016, and evaluate the admissibility of such evidence in light of evidentiary principles and the role of digital forensics. Employing a normative juridical approach, the analysis is based on statutory regulations, judicial decisions, and relevant legal scholarship. The findings reveal that while electronic evidence has been formally acknowledged through the Electronic Information and Transactions (ITE) Law and reinforced by the Constitutional Court’s decision, significant challenges persist in both its technical implementation and legal admissibility in court proceedings. Digital forensics plays a critical role in safeguarding the integrity and reliability of electronic evidence. The study concludes that reforming the Indonesian Criminal Procedure Code and developing standardized digital evidence protocols are essential to ensuring justice and legal certainty.